Permselective properties of polystyrene opal films at diamond electrode surfaces. - Sawangphruk, M; Foord, J (2010)
The permselective properties of stable opal films formed by polystyrene nanospheres on boron-doped diamond (BDD) electrodes were studied for the first time by means of electrochemical voltammetric and impedance techniques. Films formed from spheres with a diameter above 200 nm are highly porous and have little influence on electrochemical properties. In contrast, porous films formed from 50 nm spheres have a selective influence on the electrochemistry observed, providing an enhancement in the redox peak current for neutral (ferrocenemethanol, dopamine) and positively-charged redox probe mediators (Ru(NH(3))(6)(3+)) and suppressing the current due to a negatively-charged redox species Fe(CN)(6)(4-). This is because the latter is repelled from the film, whereas the former are selectively partitioned within it. Partition coefficients, film permeability and diffusion coefficients of species within the polystyrene opal layer are determined. It is shown that a Langmuir isotherm analysis for adsorption on the polystyrene sphere surface can describe successfully the incorporation of ferrocenemethanol and Ru(NH(3))(6)(3+) within the thin film, with Gibb's free energies (DeltaG(o)) of adsorption in the range of -27 to 28 kJ mol(-1). Apart from influencing the magnitude of the detected electrochemical response, it is also shown the opal film increases the resistance to electrode fouling by the reaction products formed by the oxidation of dopamine. Electrochemical impedance measurements further illustrate the effects of the polystyrene layer.